Assessing the potential conditioning effects of mis and disinformation self-efficacy on the relationship between general social media use and political knowledge - Hopp, Toby; Kazmi, Saima (Frontiers in Psychology, 2023)
Prior work on the relationship between general social media use and political knowledge has yielded mixed findings. One recent meta-analysis on the topic concluded that the literature, when assessed as a whole, fails to indicate a direct and statistically identifiable between relationship general social media use and political knowledge. Considering these findings, the present work sought to assess the extent to which general social media use might be conditionally related to political knowledge. To do so, we explored the moderating effect of information-related self-efficacy beliefs. Specifically, building upon general self-efficacy theory and the idea that there exists considerable concern over the extent to which information on social media is factually incorrect, misleading, or biased, we predicted that mis-and dis-information self-efficacy (MDSE) beliefs would positively condition the relationship between general social media usage and political knowledge. Contrary to our expectations, the results of three studies indicated that the combination of MDSE and frequent social media use was negatively related to political knowledge.